Proceedings of the 4th International Conference on Higher Education Advances (HEAd'18) 2018
DOI: 10.4995/head18.2018.8231
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic students: from language learning to language testing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some dyslexic students might not have difficulties with comprehension, but with expression of their intended meaning both in speaking and writing. Hence, in relation to writing activities, Pelleriti (2018) suggested that "students should not be penalized for their often-illegible handwriting and/or for spelling mistakes" (p.1488). Hence, the actions that need to be taken with the aim of improving the teaching process refer not only to lessons and lectures, but also to the assessment process.…”
Section: Dyslexia and Language Learningmentioning
confidence: 99%
“…Some dyslexic students might not have difficulties with comprehension, but with expression of their intended meaning both in speaking and writing. Hence, in relation to writing activities, Pelleriti (2018) suggested that "students should not be penalized for their often-illegible handwriting and/or for spelling mistakes" (p.1488). Hence, the actions that need to be taken with the aim of improving the teaching process refer not only to lessons and lectures, but also to the assessment process.…”
Section: Dyslexia and Language Learningmentioning
confidence: 99%